Efeitos do envelhecimento na altura óssea periimplantar - Pedro, Rejane Eliete Luz (2013)
Tooth loss is very common in the older people causing a need for a rehabilitative treatment by dental implants. The periimplant bone loss is one of the most important factors for the success of dental implants activated. Ageing, however, is associated with decreased bone metabolism; making can be a risk factor for the loss of these implants. It is known that bone loss can also be influenced by other factors such as gender, bruxism, diabetes, osteoporosis, heart disease, hypothyroidism, alcohol and smoking. This study aimed to monitor radiographic and clinically, for four years, the periimplant bone level from the installation of prostheses placed in dental implants. Were followed 18 patients, 57 patients with dental implants with their respective prosthesis installed, observing the periimplant bone height and systemic diseases present. The loss of periimplant bone height was significantly associated with a history of smoking and to be man, age was inversely associated with bone loss. Factors such as the presence of hypothyroidism, diabetes, hypertension, heart disease and osteoporosis were not associated with bone loss. There were no significant differences in nutritional parameters of patients followed. We conclude that age was a factor associated with height gain and bone that elderly male with a previous history of smoking are associated with loss of periimplant bone height.